Inorganic Carbon Leaching From a Warmed and Irrigated Carbonate Forest Soil - Schindlbacher, Andreas; Beck, Kerstin; Holzheu, Stefan; Borken, Werner (Frontiers in Forests and Global Change, 2019)
The response of dissolved inorganic carbon (DIC) leaching to rising temperature and precipitation is hardly known for forest soils on carbonate bedrock. We established field lysimeters, filled with soil from a humus-rich A horizon of a Rendzic Leptosol and detrital dolomite (C horizon) and conducted a two-factorial climate manipulation (control (C), soil warming (H, +4°C), irrigation (I, +50% precipitation), soil warming and irrigation (H+I)) to examine the effects of increased temperature and precipitation on DIC and DOC leaching, soil air CO2 concentrations and soil CO2 efflux. We followed an isotopic approach to assess the biotic and abiotic DIC fractions. Soil warming (H) had no effect on DIC leaching and seepage DIC concentrations. Irrigation (I and H+I) increased annual DIC leaching by almost 100% as a matter of significantly increased seepage DIC concentrations and higher annual drainage. Isotopic partitioning of DIC fluxes suggested biogenic contributions between 60 and 100% and no significant variation with warming or irrigation. Soil warming consistently increased the soil CO2 efflux by >50% independently of irrigation treatment. Soil air CO2 concentrations were not affected by soil warming alone (H). Irrigation (I and I+H) tended to increase subsoil (18 and 32 cm depth) soil air CO2 concentrations, while topsoil (6cm) remained unaffected by irrigation. DIC leaching losses were about 4-5 times higher than DOC leaching losses, which showed a similar treatment response (I and H+I > C and H). Annual DIC leaching amounted to between 20 ± 2 (C) and 39 ± 2 (H+I) g m-2¬, representing ~ 2-5% of the total annual gaseous soil CO2 loss. Our results suggest that climate change, especially changing precipitation, could significantly affect the DIC export from carbonate forest soils, thereby affecting their carbon sequestration potential.